2017
DOI: 10.1097/ijg.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Diagnostic Capability for Glaucoma of 3-Dimensional Versus 2-Dimensional Neuroretinal Rim Parameters Using Spectral Domain Optical Coherence Tomography

Abstract: Purpose To compare the diagnostic capability of 3-dimensional (3D) neuroretinal rim parameters with existing 2-dimensional (2D) neuroretinal and retinal nerve fiber layer (RNFL) thickness rim parameters using spectral domain optical coherence tomography (SD-OCT) volume scans Materials and Methods Design Institutional prospective pilot study. Study population 65 subjects (35 open angle glaucoma patients, 30 normal patients). Observation procedures One eye of each subject was included. SD-OCT was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Previous studies have demonstrated that 3D MDB neuroretinal rim thickness has similar or better diagnostic capability for glaucoma compared to 2D RNFL thickness. 27 , 28 Taken together with our study, these findings suggest that 3D MDB neuroretinal rim thickness offers an advantage to traditional 2D RNFL thickness not only in improved diagnostic capability but also in the reduced need for repeat scanning or manual correction. Although there is a commercially available low-density protocol (BMO-MRW) that quantifies neuroretinal rim tissue, this paper may encourage SD-OCT companies to incorporate high-density protocols with associated software analysis so that clinical use of SD-OCT can reach its full potential for glaucoma care.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have demonstrated that 3D MDB neuroretinal rim thickness has similar or better diagnostic capability for glaucoma compared to 2D RNFL thickness. 27 , 28 Taken together with our study, these findings suggest that 3D MDB neuroretinal rim thickness offers an advantage to traditional 2D RNFL thickness not only in improved diagnostic capability but also in the reduced need for repeat scanning or manual correction. Although there is a commercially available low-density protocol (BMO-MRW) that quantifies neuroretinal rim tissue, this paper may encourage SD-OCT companies to incorporate high-density protocols with associated software analysis so that clinical use of SD-OCT can reach its full potential for glaucoma care.…”
Section: Discussionsupporting
confidence: 72%
“…A relatively new anatomical ONH parameter is Bruch's membrane opening minimal rim width (BMO-MRW), corresponding to the minimal distance between the BMO and the internal limiting membrane. BRO-MRW correlates well with VF functional decline and shows a similar ability to detect glaucomatous eyes compared with RNFL and ONH parameters [56,57].…”
Section: Glaucoma Diagnosismentioning
confidence: 85%
“…It is likely that disc size has greater impact at the extremes, that is, for very small or very large discs or discs of highly myopic eyes . Other similar approaches based on minimum distance mapping have confirmed the advantages it provides for glaucoma diagnostics …”
Section: Current and Emerging Oct Approaches For Quantitative Evaluatmentioning
confidence: 94%